Making Vancouver: Class, Status, and Social Boundaries, 1863-1913 - McDonald, Robert A. J. (UBC Press, 1996)
Making Vancouver is about the people of Vancouver, British Columbia. It traces the social transformation of the city and points out how Shaughnessy Heights lumber barons, Mount Pleasant trades people, and East End labourers were part of a complex society whose members exhibited sharp differences in attitudes and behaviour. In Making Vancouver, Robert McDonald depicts a western city that was neither egalitarian nor closed to opportunity. Vancouver up to the crash of 1913 was a dynamic centre. The rapidity of growth, easy access to resources, a narrow industrial base, and the homogeneous nature of its population, the majority of which was of British birth, softened the thrust towards class division inherent in capitalism. Far more powerful in directing social relations was the quest for status, creating a social structure that was no less hierarchical than that predicted by class theory but much more fluid. The social boundary that separated the working class from others is revealed as a division that for much of the pre-war boom period divided Vancouver society more fundamentally than the boundary separating labour from capital. --Publisher's description
Keywords: 15.85 history of America; British Columbia Vancouver; Canada; Classes sociales Colombie-Britannique Vancouver Histoire; History; Social classes; Social classes -- British Columbia -- Vancouver -- History; Social classes British Columbia Vancouver History; Social conditions; Sociale geschiedenis; Sozialgeschichte 1883-1913; Vancouver; Vancouver (B.C.) -- History; Vancouver (B.C.) -- Social conditions; Vancouver (B.C.) History; Vancouver (B.C.) Social conditions; Vancouver (C.-B.) Conditions sociales; Vancouver (C.-B.) Histoire